2009
DOI: 10.1051/0004-6361/200811176
|View full text |Cite
|
Sign up to set email alerts
|

Detection of X-rays from the jet-driving symbiotic star MWC 560

Abstract: Aims. We report the detection of X-ray emission from the jet-driving symbiotic star MWC 560. Methods. We observed MWC 560 with XMM-Newton for 36 ks. We fitted the spectra from the EPIC pn, MOS1 and MOS2 instruments with XSPEC and examined the light curves with the package XRONOS. Results. The spectrum can be fitted with a highly absorbed hard X-ray component from an optically thin hot plasma, a Gaussian emission line with an energy of 6.1 keV and a less absorbed soft thermal component. The best fit is obtained… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…The ionization parameter in AS 304's outflow was therefore large, contributing to the absence of low-ionization (and in this case, optical) absorption. In MWC 560, optical and UV flickering (Bond et al 1984;Tomov et al 1996;Zamanov et al 2011b;Lucy et al, in preparation;though see Zamanov et al 2011a) and hard X-rays sometimes observed from the boundary layer (Stute & Sahai 2009) indicate an accretion disk without WD surface burning (see Luna et al 2013). Thus, both hot burning (AS 304) and cooler non-burning (MWC 560) symbiotics can sustain persistent BAL outflows.…”
Section: The Bal Symbioticsmentioning
confidence: 99%
“…The ionization parameter in AS 304's outflow was therefore large, contributing to the absence of low-ionization (and in this case, optical) absorption. In MWC 560, optical and UV flickering (Bond et al 1984;Tomov et al 1996;Zamanov et al 2011b;Lucy et al, in preparation;though see Zamanov et al 2011a) and hard X-rays sometimes observed from the boundary layer (Stute & Sahai 2009) indicate an accretion disk without WD surface burning (see Luna et al 2013). Thus, both hot burning (AS 304) and cooler non-burning (MWC 560) symbiotics can sustain persistent BAL outflows.…”
Section: The Bal Symbioticsmentioning
confidence: 99%
“…The orbital period is supposed to be P orb ≈ 5.3 yr (Doroshenko, Goranskij & Efimov 1993). The most spectacular features of this object are the collimated ejections of matter with velocities of up to ∼ 6000 km s −1 (Tomov et al 1992;Stute & Sahai 2009) and the resemblance of its emission line spectrum to that of the low-redshift quasars (Zamanov & Marziani 2002).…”
Section: Introductionmentioning
confidence: 98%
“…The situation could now reverse following our recent discovery (Munari et al 2016) that MWC 560 is going through a new outburst phase, brighter than that of 1990. This has immediately prompted deep X-ray observations by Lucy et al (2016) that found a dramatic enhancement in the soft (<2 keV) X-rays, compared to the observations by Stute & Sahai (2009) obtained in 2007 when MWC 560 was in quiescence. The report on the optical outburst also prompted VLA observations that detected for the first time radio emission from MWC 560 (Lucy, Weston, & Sokoloski 2016), at least an order of magnitude enhanced over a VLA non-detection on 2014 October 2, during the quiescence preceding the current outburst.…”
Section: Introductionmentioning
confidence: 90%
“…Tomov et al (1992) and Michalitsianos et al (1993) modelled MWC 560 with a non-variable M4 giant and an accreting -and probably magnetic -white dwarf (WD), surrounded by an (outer) accretion disk, and subject to a steady optically thick wind outflow and a complex pattern of mass ejection into discrete blobs. Stute & Sahai (2009) deduced however a non-magnetic WD from their X-ray observations. A fit with a variable collimated outflow that originates at the surface of the accretion disk and that is accellerated with far greater efficiency than in normal stellar atmospheres was considered by Shore, Aufdenberg, & Michalitsianos (1994).…”
Section: Introductionmentioning
confidence: 99%